Pharmacokinetic Herb-Drug Interactions of Glipizide with Andrographis paniculata (Burm. f.) and Andrographolide in Normal and Diabetic Rats by Validated HPLC Method - Sundhani, Elza; Nugroho, Agung Endro; Nurrochmad, Arief; Puspitasari, Ika; Amalia Prihati, Dita; Lukitaningsih, Endang (MDPI, 2022)
Co-administered medicinal herbs can modify a drug’s pharmacokinetics (PK), effectiveness, and toxicity. Andrographis paniculata (Burm. f.) ethanolic extract (APE) and andrographolide (AND) (a potent CYP2C9 inducer/inhibitor) can alter the pharmacokinetic parameters of glipizide (GLZ). This study aimed to determine the potential pharmacokinetics of herb–drug interactions between GLZ and APE/AND in the plasma of normal and diabetic rats using the HPLC bioanalysis method. The glipizide bioanalytical method established with RP-HPLC/UV instrument was validated following the EMA guidelines. GLZ was administered alone and in combination with APE or AND to normal and diabetic rats. The GLZ pharmacokinetic parameters were estimated according to the correlation between concentration and sampling time using the PK solver program. A simple and rapid GLZ bioanalysis technique with a lower limit of quantitation of 25 ng/mL was developed and presented the following parameters: accuracy (error ≤ 15), precision (CV ≤ 15), selectivity, stability, and linearity (R2 = 0.998) at concentrations ranging 25–1500 ng/mL. APE administration significantly improved the Cmax and AUC0–t/AUC0–∞ GLZ values in normal and diabetic rats (p < 0.05). AND significantly reduced the bioavailability of GLZ in diabetic rats with small values of T 1/2, Cmax, and AUC0–t/AUC0–∞ (p < 0.05). This combination can be considered in administering medications because it can influence the pharmacological effects of GLZ. © 2022 by the authors.